Chapter La cesura dottrinale di fine anni Trenta. Itinerari della giuspubblicistica italiana tra fascismo e Repubblica - Gregorio, Massimiliano (Studi e saggi, 2020)
The essay aims to answer a simple but very relevant question: how could be possible that the constitutionalists who gave the most important contribution in the theoretical building of Italian constitutional democracy were the same who, only a few years before, wrote about the fascist constitutional order with sincere interest (and sometimes with real appreciation)? Political opportunism? No. The answer lies in the paths of their constitutional interpretations that reveal the existence of a real doctrinal fracture in the Italian constitutionalist culture of late Thirties, created by a new generation of jurists.